Uwagi o kobiecym i męskim sposobie opowiadania - Wyrwas, Katarzyna (Stylistyka, 2004)
In this artice author describes two different ways of storytelling in everyday conversa[1]tions. Analyse of spoken narrative texts produced by women and men points which com[1]ponents of the structure are realized and how long they are. Women are very interested to other person’s life and ussualy their stories include many details about things, people and also many quotations of interlocutor talks - that’s way women’s narratives are much lon[1]ger and more digressive than men’s. For women storytelling is often the way of expressing their emotions, therefore we can find there many digressions about narrator’s feelings, which break narrative continuity and cohesion. Men ussualy tell shorter and more cohesive stories with chronological order, caring about efficient communication. Their digressions rarely stray away from the main subject of narrative.